EVALUATION OF THE FUNCTIONAL STATE OF MUSCLES IN HIGHLY TRAINED SWIMMERS - V. A. Zaborova; K. G. Gurevich; D. B. Nikitiuk; V. N. Seluyanov; V. A. Rybakov (Кубанский научный медицинский вестник, 2016)
Evaluation of the functional state of muscles is important in medico-biological provision of highly qualified athletes. Feature of swimming is a long-term training in water and physical training aimed at muscle development to overcome various distances in the shortest time. In the work carried out performance evaluation of anthropometry, physique, body composition and functional status of muscles of upper and lower extremities in athletes-swimmers. Systematic training for sport swimming increase muscle mass by 1,2 times, compared with persons not involved in sports, primarily due to the development of the muscles of the upper shoulder girdle and upper extremities and equal, but the specific distribution of fat mass in body composition. Have swimmers indices of aerobic capacity when working with the hands was higher in men 2,7, women have 3,3 times; for the feet of men and women is 2,3 times higher than in persons not involved in sports.